Weibull-Based Design Methodology for Rotating Structures in Aircraft Engines - Erwin V. Zaretsky; Robert C. Hendricks; Sherry Soditus (International Journal of Rotating Machinery)
The NASA Energy-Efficient Engine (E3-Engine) is used as the basis of a Weibull-based life and reliability analysis. Each component's life, and thus the engine's life, is defined by high-cycle fatigue or low-cycle fatigue. Knowing the cumulative life distribution of each of the components making up the engine as represented by a Weibull slope is a prerequisite to predicting the life and reliability of the entire engine. As the engine's Weibull slope increases, the predicted life decreases. The predicted engine lives L5 (95% probability of survival) of approximately 17,000 and 32,000 hr do correlate with current engine-maintenance practices without and with refurbishment, respectively. The individual high-pressure turbine (HPT) blade lives necessary to obtain a blade system life L0.1 (99.9% probability of survival) of 9000 hr for Weibull slopes of 3, 6, and 9 are 47,391; 20,652; and 15,658 hr, respectively. For a design life of the HPT disks having probable points of failure equal to or greater than 36,000 hr at a probability of survival of 99.9%, the predicted disk system life L0.1 can vary from 9408 to 24,911 hr.